Analisis Pembiayaan Mudharabah Dan Musyarakah Terhadap Profitabilitas Bank Di PT BNI Syariah Periode 2010-2018 - Jauhariyah, Nur Anim; Ma’unah, Dwi Hanifatul (LPPM STAI Ihyaul Ulum Gresik, 2019)
The purpose of this study is to determine whether there is an influence between mudharabah financing, musyarakah financing and bank profitability. To find out the simultaneous influence between mudharabah financing and musyarakah financing on bank profitability using financing products at PT BNI Syariah. This study uses a quantitative approach. The independent variable of this research is mudharabah (X1) and musyarakah financing (X2), while the dependent variable (Y) is bank profitability. The analysis tool uses multiple linear regression with the help of SPSS software. Research Results Partially from mudharabah financing (X1) to bank profitability (Y) produces tcount> t table, t count of 3.099 t table 2.447 means that it is significant; Partially musyarakah financing (X2) to bank profitability (Y) produces tcount <ttable, tcount of 0.218 and ttable 2.447 means that it is not significant; Simultaneously mudharabah financing (X1) and musyarakah financing (X2) to bank profitability (Y) produce Fcount value of 6,800 while Ftable is 5.14, then Fcount> Ftable means that it is significant that the variable mudharabah financing (X1) and musyarakah financing (X2 ) significant effect on profitability (Y) in PT BNI Syariah Period 2010-2018